Aktualna sodna praksa v zvezi z delovnimi in uslužbenskimi razmerji - Kogej Dmitrovič, Biserka (Podjetje in delo, 2021)
The article on current case law presents the legal and regulatory arrangements regarding deadlines, i.e. procedural deadlines and deadlines for exercising the rights of parties in court proceedings during the declared epidemic. The case law of the Higher Labour and Social Court regarding disputes that arose during the declared epidemic is presented. Judicial decisions on procedural and substantive issues in disputes due to termination of the employment contract, breaches of work obligations and cessation of need for labour, as well as decisions on procedural issues running procedural deadlines and deadlines for filing a lawsuit in labour disputes are summarised. There is no Supreme Court case law for such disputes yet. The second part presents the Supreme Court case law in disputes between civil servants regarding classification in salary grades, allowances for special working conditions, temporary posting, transfer of annual leave, and reimbursement of training costs in the event of termination of employment.
Keywords: allowances; classification in salary grade; deadline; deadline for exercising the rights of clients in court proceedings; dodatki; epidemic; epidemija; neizrabljen letni dopust; povračilo stroškov usposabljanja; procedural deadline; procesni rok; reimbursement of training costs; rok za uveljavljanje pravic strank v sodnih postopkih; soldiers; tek roka; temporary posting; unused annual leave; uvrstitev v plačni razred; vojaki; začasna napotitev